PENGEMBANGAN ALAT UKUR TES LITERASI SAINS SISWA SMP DALAM KONTEKS BUDAYA BALI - Sudiatmika, A.A Istri Rai (2010)
Thestudy to develop a scientific literacy instrument in the Context of Balinese Culture involved a number of students of grade IX of Public Junior High Schools (n=1648) from three regencies with stratified and proportionalsampling. The scientific literacy items refer to Program for International Student Assessment (PISA) to access the scientific literacy level of 15 year old students, but with its arrangement adjusted to the student's school level proximity. Three science dimensions that were developed comprise: 1) Science content (concept comprehension needed in science process); 2) Science process (mental processesthat is needed to comprehend science concept and science process); and 3) Science context (science knowledge application and science process usage in situations that reflectsa real condition in local science, national science, and global science). Forty items of multiple choice type with 4 options, accompanied by an explanationwere developed to discover that scientific literacy ability of students in the context of Balinese culture. The accuracy of items was analyzed through content validity, difficulty index, distinguishing factor capacity, item validity, item script reliability, and distractor quality using ANATES and ITEMAN programs. Thirty-five itemsof scientific literacyin the context of Balinese culture(19 items of local science, 8 items of national science and 8 items of general science) are found to have a accuracy to identify local, national, and also global science aspects. The items of local science are related to Balinese traditional architecture, traditional games, ceremonies of Hindu religion, traditional medication, and traditional Balinese music.Local science concepts in Bali culture contain scientific concept that are prevailed universally so that local science of Bali culture can be integrated into the learningof science.